2020
DOI: 10.1155/2020/9469210
|View full text |Cite
|
Sign up to set email alerts
|

Possible Epigenetic Role of Vitexin in Regulating Neuroinflammation in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) has been clinically characterized by a progressive degeneration of neurons which resulted in a gradual and irreversible cognitive impairment. The accumulation of Aβ and τ proteins in the brain contribute to the severity of the disease. Recently, vitexin compound has been the talk amongst researchers due to its pharmacological properties as anti-inflammation and anti-AD. However, the epigenetic mechanism of the compound in regulating the neuroinflammation activity is yet to be fully elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…These epigenetic mechanisms comprise histone methylation and acetylation, as well as miRNA. Several approaches targeting epigenetic regulation of microglia/macrophage function were proposed, including modulation of epigenetic code readers-bromodomain and extraterminal domain (BET) proteins [32][33][34][35]. The selected signaling molecules, both cell surface-bound and soluble, that are involved in the cross-talk between neurons and microglia.…”
Section: Figurementioning
confidence: 99%
“…These epigenetic mechanisms comprise histone methylation and acetylation, as well as miRNA. Several approaches targeting epigenetic regulation of microglia/macrophage function were proposed, including modulation of epigenetic code readers-bromodomain and extraterminal domain (BET) proteins [32][33][34][35]. The selected signaling molecules, both cell surface-bound and soluble, that are involved in the cross-talk between neurons and microglia.…”
Section: Figurementioning
confidence: 99%
“…Vitexin, found in several medicinal plants such as hawthorn, pearl millet, and Ficus deltoidea , regulates neuroinflammation and possesses a neuroprotective effect. Vitexin epigenetically regulates the proinflammatory cytokines and can be considered a potential candidate for the treatment of DLB and other neurodegenerative diseases [ 85 ].…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Vitexin is a flavone glycoside considered an important flavonoid of interest that possesses ample pharmacological benefits. [5] It is reported that vitexin serves as an excellent anti-inflammatory pharmakon, which reduces the level of cytokine expression at the site of inflammation. [6] TNF α is an important cytokine that plays a crucial role in the immune system's signaling pathways and inflammation.…”
Section: Abstract a R T I C L E I N F Omentioning
confidence: 99%